How Consciousness Manifests Itself. A Person’s Ability to Hypothesize - Sabadash, Kateryna (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2021)
The study examines the nature of consciousness from the point of view of its manifestations at three levels of cognition. The epistemological experience of researching the Plato’s and Kant’s thinking is analyzed. Through the hierarchy of cognizable entities, described by Plato, the difference in levels of cognition is determined. The causality of the physical world, as a cognizable structure of the empirical component of reality, not only lends itself to study, but also turns out to be subject to changes by a person. Consideration of the causal structure, due to the rational level of knowledge, makes it possible to determine the existing connection, in view of the ability to go beyond causality. The main issue is the possibility of the creation of a hypothesis as a personal ability of a conscious being. Intelligent cognition, which enables intuitive assumptions, is characteristic only of consciousness in its manifestation (human). The antinomies described by Kant are not knowledge, they unite them (knowledge) into a single understanding. The hypothesis seems to be possible only thanks to consciousness, which, when embodied, is capable of giving a person an understanding of a single first principle and cognition of empirical causation.